Assembly process and optical performances for a golden laser spark-plug device - Ribes-Pleguezuelo, Pol; Pavel, Nicolaie; Beckert, Erik; Damm, Christoph; Bodemann, Axel; Grigore, Oana-Valeria; Croitoru, Gabriela; Brandus, Catalina-Alice; Vasile, Nicolae-Tiberius; Eberhardt, Ramona; Tuennermann, Andreas (Optical Engineering, 2019)
The low-stress Solderjet Bumping technique was employed to assemble the optical components of an increased-robustness laser spark-plug ignition device using the low melting alloys 96.5Sn3Ag0.5Cu and 80Au20Sn. A finite-element-method analysis, optical simulations, and a soldering parametrization test were performed to prove that different optical materials (sapphire, ECO-550, D-ZLaF52LA, TAC4, and N-SF11 glasses) could be fastened to the stainless steel body. The assembled spark-plug device featured a passively Q-switched Nd: YAG/Cr4 +: YAG composite ceramic medium and delivered laser pulses with energy variable between 2.40 and 4.70 mJ, with 0.8 ns duration, suitable for inducing air breakdown phenomenon and engine combustion.
CRIS-Team Scopus Importer:2023-04-20
Keywords: air breakdown; combustion; laser ignition; Nd:YAG/Cr; Solderjet Bumping; spark plug